Contrasting Three Non-hypoglycemic Antidiabetic Drug Effects on Glycemic Control in Newly Diagnosed Type II Diabetes Mellitus: An Experimental Study - Hmood, Abdulhamza; Almasoody, Mohammed; Al-Jameel, Hameed Hussein (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Diabetes mellitus (DM) type 2 is the most public chronic, metabolic illness whose prevalence is quickly becoming high international. Insulin resistance, the essential metabolic problem leads to the development of DM type 2, is seen in about 90% of patients. AIM: The study’s aim was to compare the efficacy of three antidiabetic drugs on glycated hemoglobin. METHOD: A cross-sectional comparative study for newly diagnosed type II diabetic patients were assigned randomly into one of three conditions: Group I: Metformin consuming patients, Group II: Pioglitazone consuming patients, and Group III: Vildagliptin consuming patients. All patients were newly diagnosed. For all of them, baseline glycated hemoglobin was requested. After that, random assignment was carried out. After 3 months, glycated hemoglobin was checked and compared. RESULTS: Participants were distributed randomly into 27.9% metformin taking participants, 31.1% pioglitazone taking, and 41% vildagliptin taking patient. Findings suggested significant difference between Groups I and III (p =). Likewise, significant difference was seen between Groups II and III (p =). However, Groups I and II have comparable effects (p =). Indeed, all groups had shown significant efficacy on HbA1c. CONCLUSION: Metformin, pioglitazone, and vildagliptin had shown significant impact on HbA1c with variable degree: Metformin and pioglitazone had shown comparably similar efficacy that was exerted more significant impact on HbA1c than vildagliptin does.